Penyuluhan Bahaya Kebakaran, Komponen APAR dan Penggunaan APAR di SD As Syafiq - Putri, Eka Cempaka; Situngkir, Decy Situngkir; Millah, Izzatu Millah; Sitanggang, Ansadilla Niar Sitanggang (Universitas Andi Djemma, 2025)
Fires are disasters that can occur in industries, public facilities, and schools. Fires in schools are an aspect that is often overlooked for assessment, prevention, and control. This service method was carried out through activities to socialize the dangers of fire, the components of fire extinguishers, and the use of fire extinguishers to 8 teachers and 21 students. As a form of evaluation, a pretest and post-test were conducted for this activity. The results of the post-test and pre-test evaluations showed a significant difference in scores before and after the socialization activities were conducted. The analysis of each question revealed that the highest percentage of correct answers was related to the danger of electricity as a cause of fires, while the question about the steps for using an APAR received the lowest percentage of correct answers. The community service activities went well, and both teachers and students understood the outreach activities that had been conducted. It is necessary to conduct regular outreach activities on the use of fire extinguishers and open flames, establish safe muster points, and carry out evacuation simulation activities in the next community service activities.